Optimal systolic blood pressure target, time to intensification, and time to follow-up in treatment of hypertension: population based retrospective cohort study. (5th February 2015) - Xu, Wenxin; Goldberg, Saveli I; Shubina, Maria; Turchin, Alexander
Abstract : Objectives To investigate the optimal systolic blood pressure goal above which new antihypertensive medications should be added or doses of existing medications increased ("systolic intensification threshold") and to determine the relation between delays in medication intensification and follow-up and the risk of cardiovascular events or death. Design Retrospective cohort study. Setting Primary care practices in the United Kingdom, 1986-2010. Participants 88 756 adults with hypertension from The Health Improvement Network nationwide primary care research database. Main outcome measures Rates of acute cardiovascular events or death from any cause for patients with different hypertension treatment strategies (defined by systolic intensification threshold, time to intensification, and time to follow-up over the course of a 10 year treatment strategy assessment period) after adjustment for age, sex, smoking status, socioeconomic deprivation, history of diabetes, cardiovascular disease or chronic kidney disease, Charlson comorbidity index, body mass index, medication possession ratio, and baseline blood pressure. Results During a median follow-up of 37.4 months after the treatment strategy assessment period, 9985 (11.3%) participants had an acute cardiovascular event or died. No difference in risk of the outcome was seen between systolic intensification thresholds of 130-150 mm Hg, whereas systolic intensification thresholds greater than 150 mm Hg were associated with progressively greater risk (hazard ratio 1.21, 95% confidence interval 1.13 to 1.30; P<0.001 for intensification threshold of 160 mm Hg). Outcome risk increased progressively from the lowest (0-1.4 months) to the highest fifth of time to medication intensification (hazard ratio 1.12, 1.05 to 1.20; P=0.009 for intensification between 1.4 and 4.7 months after detection of elevated blood pressure). The highest fifth of time to follow-up (>2.7 months) was also associated with increased outcome risk (hazard ratio 1.18, 1.11 to 1.25; P<0.001). Conclusions Systolic intensification thresholds higher than 150 mm Hg, delays of greater than 1.4 months before medication intensification after systolic blood pressure elevation, and delays of greater than 2.7 months before blood pressure follow-up after antihypertensive medication intensification were associated with increased risk of an acute cardiovascular event or death. These findings support the importance of timely medical management and follow-up in the treatment of patients with hypertension.